At-risk youths' self-sufficiency: The role of social capital and help-seeking orientation. (August 2018) - Schenk, Loïs; Sentse, Miranda; Lenkens, Margriet; Engbersen, Godfried; van de Mheen, Dike; Nagelhout, Gera E.; Severiens, Sabine
Abstract: Youths' help-seeking orientation on the individual level, and the presence of bonding and bridging social capital at the contextual level, are important factors in explaining at-risk urban youths' self-sufficiency. We conducted semi-structured interviews with 22 at-risk youths aged 15–25 years in an urban area, to study youths' perceptions of help-seeking and social capital. Consequently, we attempted to uncover the associations between these concepts. The results indicate that only few youths had positive help-seeking orientations, irrespective of their preference for self-reliance. Sources of help that youths feel comfortable to activate in their immediate environment are limited, but support is also found in extended family members. Bridging social capital is mainly provided by professionals and comprises instrumental and informational support. Many youths believe they can be understood only by individuals who are similar to them, but simultaneously indicate a need for additional support from significant others. Highlights: Youths have positive experiences of informational and instrumental support from bridging contacts with perceived similarities. Youths are hesitant to activate parental support sources, but receive additional support from extended family members. Positive help-seeking orientation is shaped by positive experiences and is not necessarily hindered by self-reliance. Self-sufficiency could be stimulated by considering youths' need for self-reliance and by expanding bridging social capital.